1144 Actigraphy-defined Sleep And Neurocognitive Decline In Middle-age Hispanic/Latino Adults. (27th May 2020) - Agudelo, C; Tarraf, W; Wu, B; Wallace, D M; Patel, S R; Redline, S; Daviglus, M L; Zee, P C; Simonelli, G; Levin, B E; Mossavar-Rahmani, Y; Sotres-Alvarez, D; et al.
Abstract: Introduction: Few studies have evaluated objective sleep measures and longitudinal neurocognitive decline, particularly in middle-age or Hispanic/Latino adults. We evaluated prospective associations between actigraphy-defined sleep and 7-year neurocognitive change among Hispanic/Latino adults. We hypothesized that sleep duration would be associated with neurocognitive decline. Methods: We analyzed data from 1, 036 adults 45-64 years of age from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL), a multi-center prospective cohort study of diverse community-dwelling Hispanic/Latino adults. At Visit 1 (2008-2011), participants underwent neurocognitive assessments, 7-days of actigraphy, home sleep testing, and sleep questionnaires (including the Insomnia Severity Index). Seven years later, participants repeated neurocognitive assessments. The neurocognitive battery included the Six-Item Screener, Brief Spanish-English Verbal Learning Test, phonemic word fluency test, and Digit Symbol Subtest. Survey linear regression was used to evaluate prospective associations between actigraphy-defined or self-reported sleep variables and neurocognitive change. Final models adjusted for objectively-defined variables (age, body-mass index, Field Center, and time between neurocognitive assessments), and self-reported variables (sex, education, Hispanic/Latino background, alcohol consumption, physical activity, heart failure, cerebrovascular events, depression and anxiety symptoms, and antidepressant use). Results: At Visit 1, the sample was 55% female and mean age was 54.9±2.2 years. The mean sleep duration was 402.6±27.6 minutes, mean sleep-onset latency was 11.3±9.7 minutes, mean number of days with naps of ≥ 15 minutes duration was 1.1±0.7, and mean sleep-time per nap was 51±14.1 minutes. Increased sleep-onset latency was associated with 7-year declines in global neurocognitive function (β=-0.0026, p<0.01), verbal learning (β=-0.0028, p<0.001) and verbal memory (β=-0.036, p<0.05). Increased sleep-time per nap predicted better verbal memory (β=0.0038, p<0.05). In contrast, sleep duration, sleep fragmentation, and self-reported sleep measures were not associated with neurocognitive change. Conclusion: Among middle-age adults, sleep-onset latency and nap duration were associated with neurocognitive change. These findings may serve as targets for intervention of neurocognitive decline. Support: This work is supported by the National Institute on Aging: R01AG048642, RF1AG054548, R01AG061022, R21AG056952, and R21HL140437 (AR).